UPAYA GURU SEJARAH DALAM MENYIASATI TUNTUTAN PEMANFAATAN ICT DALAM PEMBELAJARAN DI SEKOLAH MENENGAH ATAS (Paramita: Historical Studies Journal, 2013)
This study aims to analyze the use of ICT, the obstacles and the efforts made by teachers in the learning of history. It took place at Senior High School in Surakarta using interviews, observation and document review methods. The results show that there are teachers who are really active but there are also some others who are very rare in using ICT. Generally ICT especially the Internet is used by the teachers to supplement the materials that do not exist in textbooks and to search for images as a learning medium, especially those that can not be made by them. For students, the source of the Internet is to fulfill the tasks given by the teacher. The obstacles encountered by the history teachers in dealing with the progress of ICT in the learning of history come from the teachers, students, schools, and studentsâ€™ parents. The efforts conducted by the history teachers to address those obstacles are by giving assignments, asking for help from others and completing the software.Keywords: history teacher, ICT, learning of history Â Penelitian ini bertujuan menganalisis pemanfaatan ICT, kendala-kendala dan upaya yang dilakukan oleh guru dalam pembelajaran sejarah. Penelitian mengambil lokasi di SMA Kota Surakarta dengan menggunakan metode wawancara, observasi dan kajian dokumen. Hasil penelitian menunjukkan bahwa ada guru yang begitu aktif tetapi masih ada pula yang sangat jarang menggunakan ICT. Secara umum ICT terutama internet digunakan oleh guru untuk melengkapi materi yang belum ada di buku teks dan untuk mencari gambar sebagai media pembelajaran, khususnya gambar yang tidak bisa dibuat sendiri. Bagi siswa, sumber dari internet adalah untuk memenuhi tugas yang diberikan guru. Kendala yang ditemui guru sejarah dalam menyiasati kemajuan ICT pada pembelajaran sejarah berasal dari guru, siswa, sekolah, dan orang tua siswa. Upaya yang dilakukan guru sejarah untuk mengatasi kendala-kendala itu adalah dengan penugasan, meminta bantuan orang lain dan melengkapi perangkat lunak. Kata kunci: guru sejarah, ICT, pembelajaran sejarah